Application of Halaqah Tahfidz Qur'an Extracurricular Activities Specifically in the Formation of Religious Behavior of Santriwati Ar-Rohmah Ngawi Islamic Boarding School - Dian Febrianingsih (STAI Miftahul Ula Nganjuk, 2020)
This study aims to determine the implementation of extracurricular activities halaqah tahfidz Qur'an specifically at the female Islamic boarding school Ar Rohmah Ngawi, analyze the religious behavior of female students who take part in extracurricular activities halaqah tahfidz Qur'an specifically and find out the supporting and inhibiting factors that influence the application of religious behavior of female students in Ar Rohmah Islamic boarding school for girls participating in special extracurricular activities, halaqah tahfidz Qur'an. Collecting data using the method of observation, interviews and documentation. Data analysis techniques through data triangulation, namely analyzing the results of interviews by checking the validity of the data which includes data sources, methods and time. The results of this study stated that the halaqah tahfidz Qur'an extracurricular activities specifically at the Ar Rohmah Ngawi female Islamic boarding school handled female students who had specialties in memorizing the Qur'an exceeding the targets programmed for each class and motivating them with various additional activities to strengthen memorization Qur'an for female students so that they are expected to graduate with memorization of 30 chapters of the Qur'an. Analysis of religious behavior at the female Islamic boarding school Ar Rohmah Ngawi shows that learning at the female Islamic boarding school Ar Rohmah Ngawi always begins with greetings and prayers. Praying before studying is an embodiment of morality to Allah SWT in learning, while at the same time praying to Allah SWT is a manifestation of a straight Islamic faith. Supporting factors in the application of religious character at the Ar Rohmah Ngawi Islamic boarding school include supporting facilities, togetherness between teachers, female students can use the environment as a trigger for a learning atmosphere, female students memorize the Qur'an as a calming agent, have good management and the existence spirit of the students. The inhibiting factors found in the field were lack of attention and cooperation from some parents of students, limited teaching media, lack of knowledge of child psychology, boredom of female students when participating in extracurricular activities, especially those that are mandatory, halaqah tahfidz Qur'an, and problems that arise. due to personal matters of students.